Trivial pursuit media as an effort to increase knowledge of dental health maintenance in elementary school children - Lovely, Arfiani Puspita; Purnama, Tedi; RE, Pudentiana Rr; Ngatemi, Ngatemi; Kasihani, Ni Nyoman (Journal Center of Excellent : Health Assistive Technology, 2026)
Background: Data from the 2023 Indonesian Health Survey shows that over the past year, half of the Indonesian population aged over 3 years old has had oral and dental health issues. Knowledge about good oral health can prevent oral and dental issues. That is why oral and dental health education is very important, especially at the elementary school age. The application of suitable media for learning and methods of counseling might improve students’ knowledge. This study uses the trivial pursuit game as a learning instrument to improve knowledge about how to maintain the oral and dental health. Objective: to analyze the effectiveness of trivial pursuit media as an effort to increase knowledge of dental health maintenance in elementary school children. Method: This study uses a pre-experimental method with a one group pre-test post-test design. Data analysis used a paired sample t-test. Results: This study shows an average of the knowledge score about how to maintain oral and dental health before playing with the trivial pursuit game of 70.53 and after playing of 93.77, with a p-value of 0.001 (p < 0.05) Conclusion: Trivial Pursuit media effectively increases knowledge of dental health maintenance in elementary school children